Knowledge, language, and communication in Heraclitus - de Zubiría Rueda, Manuel (The University of Edinburgh, 2019)
The main objective of this thesis is to provide an interpretation of Heraclitus’ epistemology in connection with his ideas of language and communication. It proposes an interpretation of his philosophical doctrine that focuses on answering two interrelated epistemological questions: what is knowledge in Heraclitus’ doctrine? And how do we acquire it? These two main questions imply four other questions that treat the problem of the role that language and communication play in pursuing and understanding knowledge: why does Heraclitus consider that people fail to understand? Is our language a suitable medium to communicate knowledge to others? Is the way in which Heraclitus uses language, his obscure style, important in this process? What do people need to do in order to understand? The thesis is divided in four main sections. First, I offer a general introduction to the study of Heraclitus, where I argue that many of his fragments and his philosophical doctrines point to the problem of knowledge, its acquisition, and communication. Second, I argue that the object of knowledge in Heraclitus’ epistemology is the logos, an independent, eternal, divine, cosmic, and complete description of the cosmos, which cannot be directly communicated to other people. Third, I propose that such an idea of logos implies that Heraclitus had a theory of correctness of names: in the logos everything is described correctly. However, language is not a suitable medium to directly communicate this logos among humans. As a result, Heraclitus proposes the solution of referring and pointing to this logos indirectly, by using analogies, allegories, and different puns and word play. Lastly, I argue that people, and in particular their souls, are an important part of the process of knowledge. Heraclitus sees soul as material (by default) and locates it within his cosmology. Most importantly, he attributes several physiological and psychological functions to the human soul. I propose that, while Heraclitus cannot tell us the logos directly, he can direct us to it and help us in realising that our personal logoi are wrong, which makes our souls ‘barbarian’ and unable to properly understand the world reported to us by our senses and its true logos.
Keywords: Heraclitus of Ephesus; knowledge; logos; epistemology; Ancient Philosophy